    ### Answers − Solving Equations, Multiplication and Division 1

#### 1.   If 7 y = 21, what is the value of y?

The inverse of × 7 is ÷ 7. So divide both sides by 7

 7 y = 21 ÷ 7 = ÷ 7

 y = 3

To verify, put the value of y = 3 back into the original equation
7 × 3 = 21

#### 2.   If 5 a = 55, what is the value of a?

The inverse of × 5 is ÷ 5. So divide both sides by 5

 5 a = 55 ÷ 5 = ÷ 5

 a = 11

To check, put the value of a = 11 back into the original equation
5 × 11 = 55

#### 3.   If 6 z = 42, solve z

The inverse of × 6 is ÷ 6. So divide both sides by 6

 6 z = 42 ÷ 6 = ÷ 6

 z = 7

To verify, put the value of z = 7 back into the original equation
6 × 7 = 42

#### 4.   If 9 y = 36, what is the value of y?

The inverse of × 9 is ÷ 9. So divide both sides by 9

 9 y = 36 ÷ 9 = ÷ 9

 y = 4

To check, put the value of y = 4 back into the original equation
9 × 4 = 36

#### 5.   If 8 z = 24, solve z

The inverse of × 8 is ÷ 8. So divide both sides by 8

 8 z = 24 ÷ 8 = ÷ 8

 z = 3

To verify, put the value of z = 3 back into the original equation
8 × 3 = 24

#### 6.   If y/8 = 5, what is the value of y?

The inverse of ÷ 8 is × 8. So multiply both sides by 8

 y/8 = 5 × 8 = × 8

 y = 40

To check, put the value of y = 40 back into the original equation
40 ÷ 8 = 5

#### 7.   If b/8 = 7, solve b

The inverse of ÷ 8 is × 8. So multiply both sides by 8

 b/8 = 7 × 8 = × 8

 b = 56

To verify, put the value of b = 56 back into the original equation
56 ÷ 8 = 7

#### 8.   If y/9 = 6, what is the value of y?

The inverse of ÷ 9 is × 9. So multiply both sides by 9

 y/9 = 6 × 9 = × 9

 y = 54

To check, put the value of y = 54 back into the original equation
54 ÷ 9 = 6

#### 9.   If z/4 = 9, solve z

The inverse of ÷ 4 is × 4. So multiply both sides by 4

 z/4 = 9 × 4 = × 4

 z = 36

To verify, put the value of z = 36 back into the original equation
36 ÷ 4 = 9

#### 10.   If b/3 = 25, what is the value of b?

The inverse of ÷ 3 is × 3. So multiply both sides by 3

 b/3 = 25 × 3 = × 3

 b = 75

To check, put the value of b = 75 back into the original equation
75 ÷ 3 = 25 back to:   